Pendekatan Teori Permainan Potensial untuk Manajemen Interferensi pada Jaringan Makro-Femto - I Wayan Mustika; Bagus Made Sabda Nirmala; Selo Sulistyo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
In the present paper, a dynamic resource allocation scheme in orthogonal frequency-division multiple access (OFDMA) femtocells is proposed. In the proposed scheme, each femto base station dynamically selects the most appropriate subset of resource blocks (RBs) in a decentralized manner in order to mitigate the downlink cross- and co-tier interference. A game theoretic approach is used to model the interactions among autonomous entities, where each player attempts to maximize its own utility by choosing the best subset of RBs among the available RBs. The proposed utility function captures the cooperative behavior to manage the cross- and co-tier interference, which can be formulated as a potential game and demonstrated to converge to a Nash equilibrium. The simulation results show that the proposed scheme guarantees the convergence to Nash equilibrium and facilitates the femtocells to improve the throughput where the average 50% of user throughput above 7.3 Mbps, while minimizing the cross-tier interference to the macrocell network.